Strategi Pencegahan dan Penanganan Kekerasan Seksual pada Perguruan Tinggi Swasta Universitas 17 Agustus 1945 Surabaya - Permana, Ferditya Ilham; Hertati, Diana (IAI Nasional Laa Roiba Bogor, 2025)
Preventing and handling sexual violence in every tertiary institution is a very important issue and requires appropriate and comprehensive steps in implementing the prevention and handling of violence in the tertiary environment. Universities are fully responsible for protecting the academic community from all forms of violence, especially sexual violence. This strategy is also designed to prevent, detect and handle cases of sexual violence systematically and sustainably. So that the community and campus residents as objects in a policy for preventing and handling sexual violence are one of the main reasons for the formation of regulations for the Prevention and Handling of Violence in Higher Education Environments (PPKPT) which have been formed in Permendikbudristek No. 55 of 2024 as a more complete replacement for Permendikbudristek No. 30 of 2021 concerning Prevention and Handling of Sexual Violence (PPKS).